Paternal dietary ratio of n-6: n-3 polyunsaturated fatty acids programs offspring leptin expression and gene imprinting in mice - Shi, Qiaoyu; Liu, Xuanyi; Fan, Xiuqin; Wang, Rui; Qi, Kemin (Frontiers in Nutrition, 2022)
This study determined the effects of the paternal dietary ratio of n-6:n-3 polyunsaturated fatty acids (PUFAs) on leptin expression in the offspring and associated gene imprinting in a mouse model. Three- to four-week-old male C57BL/6J mice (F0) were fed an n-3 PUFA-deficient (n-3 D) diet, a diet with normal n-3 PUFA content (n-3 N; n-6:n-3=4.3:1), or a diet with a high n-3 PUFA content (n-3 H; n-6:n-3=1.5:1) for 8 weeks. Two subsequent generations were generated by mating F0 and F1 male mice with 10-week-old virgin female C57 BL/6J mice, to produce F1 and F2 offspring. Compared to the paternal n-3 D diet, paternal n-3 N and n-3 H diets reduced adipose mRNA expression of leptin (Lep) and its plasma concentrations in juvenile F1 male and female offspring, and adult F1 male and F2 female offspring, with upregulated Lep receptor mRNA expression in the hypothalamus. Meanwhile, paternal n-3 N and n-3 H diets altered the expression of imprinted genes H19, Igf2, Igf2r, Plagl1, Cdkn1c, Kcnq1ot1, Peg3, and Grb10 in the adipose tissue of juvenile and adult F1 males, with almost no effects on F1 females, while more effects were observed in the adult F2 females than F2 males. Principal component analysis verified that Plagl1, Cdkn1c, and Kcnq1ot1 contributed the most to variation in adipose tissue expression in all offspring. Some of these genes (Plagl1, Cdkn1c, Kcnq1ot1, Peg3, and Grb10) were altered by the paternal n-3 N and n-3 H diets in the F1 and F2 generation testes as well. Furthermore, adipose Lep expression was positively correlated with expressions of H19, Igf2r, Plagl1, and Kcnq1ot1 in juvenile F1 males and females, negatively correlated with the Kcnq1ot1 expression in adult F1 males, and positively correlated with the Plagl1 expression in adult F2 females. These data imply that paternal Plagl1, Cdkn1c, and Kcnq1ot1 might be part of the pathways involved in offspring leptin programming. Therefore, a lower ratio of n-6:n-3 PUFAs, with higher intake of n-3 PUFAs in paternal pre-conception, may help maintain the offspring’s optimal leptin pattern in a sex-specific manner through multiple generations, and thereby, be beneficial for the offspring’s long-term health.